Oral Amylin Treatment Reduces the Pathological Cascade of Alzheimer's Disease in a Mouse Model. (16th June 2021) - Na, Hana; Tian, Hua; Zhang, Zhengrong; Li, Qiang; Yang, Jack B.; Mcparland, Liam; Gan, Qini; Qiu, Wei Qiao
Intraperitoneal injection of amylin or its analog reduces Alzheimer's disease (AD) pathology in the brains. However, self-injecting amylin analogs is difficult for patients due to cognitive deficits. This work aims to study the effects of amylin on the brain could be achieved by oral delivery as some study reported that amylin receptor may be present in the gastrointestinal tract. A 6-week course of oral amylin treatment reduced components of AD pathology, including the levels of amyloid-β, phosphorylated tau, and ionized calcium binding adaptor molecule 1. The treatment reduced active forms of cyclin-dependent kinase 5. Oral amylin treatment led to improvements in social deficit in AD mouse. Using immunofluorescence, we observed the amylin receptor complexed with the calcitonin receptor and receptor activity-modifying proteins in the enteric neurons. The study suggests the potential of the oral delivery of amylin analogs for the treatment of AD and other neurodegenerative diseases through enteric neurons.